Panen Raya Dan Dampaknya Terhadap Kesejahteraan Dan Pola Konsumsi Petani Di Desa Payabakung Kecamatan Hamparan Perak - Nursamsi, Nursamsi; Rukman, Alghif Aruni Nur; Syahftra, Muhammad (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
This research aims to analyze the impact of the harvest on the welfare and consumption patterns of farming households. The research location is in Paya Bakung village, Hamparan Perak sub-district, Deli Serdang Regency, North Sumatra. The data analysis method used is descriptive and tests the difference between the average consumption of farmer households during the main harvest and non-harvest periods using a paired sample t-test with a confidence level of 95%. The research results show a decrease in the price of farmers' grain by 24.3% to IDR 3,700/kg GKP during the harvest season.Â The Farmer's Exchange Rate (NTP) at harvest time was 58.25%, meaning farmers were not prosperous. In terms of consumption patterns, there has been a decrease in consumption of staple foods such as fish, sugar, fruit, and fuel (LPG), while there has been no change in rice, cooking oil, and vegetables. There are differences in food consumption by farming households during non-harvest times and during peak harvest times.